Asthma control in Latin America: the Asthma Insights and Reality in Latin America (AIRLA) survey. - Neffen, Hugo (2005)
Objectives. The aims of this survey were (1) to assess the quality of asthma treatment and control in Latin America, (2) to determine how closely asthma management guidelines are being followed, and (3) to assess perception, knowledge and attitudes related to asthma in Latin America. Methods. We surveyed a household sample of 2 184 adults or parents of children with asthma in 2003 in 11 countries in Latin America. Respondents were asked about healthcare utilization, symptom severity, activity limitations and medication use. Results. Daytime asthma symptoms were reported by 56% of the respondents, and 51 % reported being awakened by their asthma at night. More than half of those surveyed had been hospitalized, attended a hospital emergency service or made unscheduled emergency visits to other healthcare facilities for asthma during the previous year. Patient perception of asthma control did not match symptom severity, even in patients with severe persistent asthma, 44.7% of whom regarded their disease as being well or completely controlled. Only 2.4% (2.3% adults and 2.6% children) met all criteria for asthma control. Although 37% reported treatment with prescription medications, only 6% were using inhaled corticosteroids. Most adults (79%) and children (68%) in this survey reported that asthma symptoms limited their activities. Absence from school and work was reported by 58% of the children and 31% of adults, respectively. Conclusions. Asthma control in Latin America falls short of goals in international guidelines, and in many aspects asthma care and control in Latin America suffer from the same shortcomings as in other areas of the world.